Penerapan Alat Sentrifugasi Dilengkapi Penyaring Sebagai Peningkatan Umur Simpan VCO di KWT Nira Lestari: Pengabdian Masyarakat Penerapan Teknologi - Muhammad Haris Yulianto; Aldi Riyanto; Farrizh Noer Abdiellah; Yasmeen Afifah Nurbakhsy; Laila Mukarromah; Ella Rizki Farihatul Maftuhah; Mokhammad Fajar Pradipta (Journal of Appropriate Technology for Community Services, 2024)
Kelompok Wanita Tani (KWT) Nira Lestari is a micro, small and medium enterprise (MSME) engaged in coconut processing, including Virgin Coconut Oil (VCO). VCO products produced by partners have low quality and quickly smell rancid. These problems are caused by the manual production process which causes a long production time, the inclusion of water that causes hydrolysis and the high volatile compounds in VCO. The purpose of this program is to design a centrifugation device and vacuum pump filter to increase the efficiency of partner production and eliminate rancid odor in the VCO produced. The method used in this service is a survey of partner needs, tool design, tool making, tool testing, tool application and product testing. The application of the two tools has been proven to help streamline partner production and eliminate rancidity. Laboratory test results of VCO after the use of the tool show that VCO has a moisture content of 0.0829% and a germ content of 0%.